Asymmetry of carbon sequestrations by plant and soil after forestation regulated by soil nitrogen - Hong, Songbai; Ding, Jinzhi; Kan, Fei; Xu, Hao; Chen, Shaoyuan; Yao, Yitong; Piao, Shilong (Nature communications, 2023)
Forestation is regarded as an effective strategy for increasing terrestrial carbon sequestration. However, its carbon sink potential remains uncertain due to the scarcity of large-scale sampling data and limited knowledge of the linkage between plant and soil C dynamics. Here, we conduct a large-scale survey of 163 control plots and 614 forested plots involving 25304 trees and 11700 soil samples in northern China to fill this knowledge gap. We find that forestation in northern China contributes a significant carbon sink (913.19 ± 47.58 Tg C), 74% of which is stored in biomass and 26% in soil organic carbon. Further analysis reveals that the biomass carbon sink increases initially but then decreases as soil nitrogen increases, while soil organic carbon significantly decreases in nitrogen-rich soils. These results highlight the importance of incorporating plant and soil interactions, modulated by nitrogen supply in the calculation and modelling of current and future carbon sink potential. Linkage between plant and soil carbon dynamics after forestation remains uncertain and controversial. Here the authors show that soil nitrogen regulates the asymmetry of carbon sequestrations by plant and soil after forestation.